2014
DOI: 10.1002/ieam.1558
|View full text |Cite
|
Sign up to set email alerts
|

Root length of aquatic plant, Lemna minor L., as an optimal toxicity endpoint for biomonitoring of mining effluents

Abstract: Lemna minor, a free-floating macrophyte, is used for biomonitoring of mine effluent quality under the Metal Mining Effluent Regulations (MMER) of the Environmental Effects Monitoring (EEM) program in Canada and is known to be sensitive to trace metals commonly discharged in mine effluents such as Ni. Environment Canada's standard toxicity testing protocol recommends frond count (FC) and dry weight (DW) as the 2 required toxicity endpoints-this is similar to other major protocols such as those by the US Environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In the past, little attention has been paid to the roots in Lemna since it was generally considered that root fragility made their handling for measurements difficult and that it was impractical to obtain sufficient numbers of individual plants with identical root lengths to initiate tests. However, more recently the ecotoxicological significance of the root endpoint has been re-evaluated and root length was shown to be a sensitive, precise and ecologically significant endpoint in comparison with more traditional frond growth and biomass endpoints (Park et al, 2013;Gopalapillai et al, 2014). Compared with results obtained from measurements of frond area, root re-growth showed paraquat to be the most toxic of the tested herbicides to all three Lemna species, with mean EC 50 values of 7.1, 7.9 and 10.6 mg L À1 for L. gibba, L. paucicostata and L. minor, respectively.…”
Section: Root Re-growthmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past, little attention has been paid to the roots in Lemna since it was generally considered that root fragility made their handling for measurements difficult and that it was impractical to obtain sufficient numbers of individual plants with identical root lengths to initiate tests. However, more recently the ecotoxicological significance of the root endpoint has been re-evaluated and root length was shown to be a sensitive, precise and ecologically significant endpoint in comparison with more traditional frond growth and biomass endpoints (Park et al, 2013;Gopalapillai et al, 2014). Compared with results obtained from measurements of frond area, root re-growth showed paraquat to be the most toxic of the tested herbicides to all three Lemna species, with mean EC 50 values of 7.1, 7.9 and 10.6 mg L À1 for L. gibba, L. paucicostata and L. minor, respectively.…”
Section: Root Re-growthmentioning
confidence: 99%
“…(see reviews by Wang, 1990). Recently, Gopalapillai et al (2014) reported root length of Lemna minor as to be the optimal endpoint for biomonitoring of mining effluents. The authors considered average root length (RL) the ideal endpoint for three reasons: accuracy (i.e., toxicological sensitivity to the contaminant), precision (i.e., lowest variance), and ecological relevance (metal mining effluents) (Gopalapillai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly sensitive stress responses on L. minor root growth were also observed in metal and pesticide toxicity. Following this, L. minor root growth/length has been suggested as an alternative bioassay for toxicity testing [ 42 , 43 , 44 ]. All endpoints, including frond biomass, frond number and frond area, showed a clear decrease at the highest tested dose rate (97 ± 8 mGy·h −1 ).…”
Section: Discussionmentioning
confidence: 99%